(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Objectives: Kopi luwak (civet coffee) is produced through a fermentation process in the digestive system of civets. This study aims to investigate the diversity of microorganisms in Indonesian civet excreta fed with robusta coffee cherries. Materials and Methods: Six excreta samples were collected from male and female Indonesian civets of three species: binturong (Arctictis binturong), Asian palm civet (Paradoxurus hermaphroditus), and masked palm civet (Paguma larvata). Microbial diversity was analyzed using next-generation sequencing. Results: Based on alpha and beta diversity analysis, the microbial community in civet excreta differs. Microbes found in the excreta of male P. hermaphroditus (PH-M) were the most diverse. Microbes were identified in the bacterial and yeast domains. The relative abundance of bacteria was higher than yeast. The occurrence of non-pathogenic bacteria (50.76%–90.51%) was higher than pathogens (9.49%–41.24%). The dominant bacteria in the excreta of all civets were Escherichia coli (15.98%–54.68%). Although not dominant microorganisms, lactic acid bacteria (LAB) and yeast are present in civet excreta. The LAB present in the range from 0.16% to 32.14%, with the most abundant LAB being Streptococcus pasteurianus, Weissella confusa, and W. cibaria. Meanwhile, the identified yeasts were Hanseniaspora opuntiae and H. uvarum. Pathogenic bacteria, both spore-forming and non-spore-forming, were also present in civet excreta. The virulence factors and antimicrobial resistance gene cluster were detected. Conclusion: The microbial diversity of Indonesian civet excreta is influenced by species and sex. PH-M contains the most diverse microbes. The presence of foodborne pathogens in civet excreta may be carried over into the beans, and hence, further processing of the beans should assure the safety of the beans. J. Adv. Vet. Anim. Res., 12(2): 565–581, June 2025 http://doi.org/10.5455/javar.2025.l921